Srikandi of Character: Strengthening Honest Behavior Through Psychoeducation at Vocational High School X Temanggung - Nurul Muntazah; Muhammad Roby; Arsita, Dina; Indhyra Hennifa Nurrochmah; Wanda Mutiarawati; Muhammad Japar (Abdi Psikonomi, 2025)
Phenomena of dishonesty among high school adolescents indicate a serious challenge in character education. At SMK X Temanggung, cases of dishonesty were found among female students who claimed menstruation as an excuse to avoid prayer due to its schedule being close to school dismissal. This reflects a tendency to choose dishonesty as well as a lack of awareness of honesty and spiritual responsibility. This community service activity employed a psychoeducation method. The results showed that the psychoeducation intervention increased the average student knowledge score on honest behavior from 70.882 to 75.588, although the difference was not statistically significant (p = 0.058). This increase indicates that psychoeducation is able to strengthen students’ cognitive aspects related to the value of honesty.